Production of major mycotoxins by fusarium species isolated from wild grasses in Peninsular Malaysia - Nor Azliza, I.; Hafizi, R.; Nurhazrati, M.; Salleh, B. (Universiti Kebangsaan Malaysia, 2014)
The Fusarium species are notoriously known for causing various plants and animal diseases and producing a number of harmful mycotoxins. The mycotoxins production by species recovered from non-agricultural hosts such as wild grasses have hitherto never been given attention. We examined 30 strains representing 12 Fusarium species i.e. F. oxysporum, F. solani, F. semitectum, F. nelsonii, F. compactum, F. equiseti, F. chlamydosporum, F. proliferatum, F. subglutinans, F. sacchari, F. lateritium and F. incarnatum-equiseti species complex isolated from wild grasses in Peninsular Malaysia for the production of four major mycotoxins i.e. moniliformin (MON), fumonisin B1 (FB1), zearalenone (ZEN) and beauvericin (BEA) using TLC and HPLC techniques. BEA was the highest frequency of mycotoxin detected, followed by MON, ZEN and FB1. This study also presented the first report of BEA production by F. solani, F. compactum and F. chlamydosporum. All mycotoxins were not produced by F. nelsonii and F. lateritium. All Fusarium species were isolated from asymptomatic grasses, hence they are likely to exist as endophytes or latent pathogens.